Indirect Negative Directive Verbs Between Arabic and Turkish - Nouray Omer Ali; Dilkhosh Jarallah Hussein Dzaey (Zanco Journal of Humanity Sciences)
Negative in directive speech verbs between the Arabic and Turkish languages by following the Pragmatic Contrastive Study in analyzing the texts circulated between the interlocutors expressing their indirect intentions, the Quranic verses and proverbs between the Arabic and Turkish languages to access the world of discourse.The contrastive study carries in its folds the contrast between two languages from two different factions, such as Arabic and Turkish, which is the purpose of our research to find out the differences and similarities between them, especially in the field of  indirect verbal verbs, which are a dimension of pragmatics, and branch out into multiple verbal categories represented by the positive, negative, interrogative and admonition verbal act that It was used in the two languages with different structural and contextual formations and similar or different connotations.The research dealt with the theoretic side at the beginning to clarify the concept of verbal verbs, and the research was drawn into the applied field by citing evidence and models